An Examination of the Reciprocal Relations Between Treatment by Others, Anger, and Antisocial Behavior: a Partial Test of General Strain Theory - Kondrat, Allison G. (Crime & delinquency, 2023)
General Strain Theory (GST) has received an impressive amount of empirical attention. However, much remains unknown about the role of sources of strain argued to be conducive to negative emotionality—such as perceived unjust treatment—on changes in anger and antisocial behavior over time. The current study aimed to begin to address this gap in the literature by assessing the relationship between changes in perceived unjust treatment, anger, and antisocial behavior across 8 years of the life course. Results from a series of auto-regressive cross-lagged models show support for GST, as well as offer evidence for new lines of empirical investigation. The reported findings offer some of the first evidence for a developmental cascade model of GST.